ANALISIS KEBIJAKAN PEMERINTAH TENTANG KESETARAAN GENDER MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2014 - Reski Lestari; Sri Ika Mulia; Syed Agung Afandi (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
In Law Number 23 of 2014 concerning Regional Government, each region is given the freedom to administer and manage its respective region. In this law, gender equality is included in mandatory government affairs that are not related to basic services. This research aims to analyze gender equality in Law Number 23 of 2014. The method used in this research is a qualitative method, with a literature approach. The research results show an analysis of Law Number 23 of 2014 where every level of government, both central government, provincial government and district/city government has a division of tasks in sub-affairs on women's quality of life, women's protection, family quality, gender and child data systems and special protection for children. Factors that influence gender equality in Law Number 23 of 2014 include gender issues in the political and legal fields, gender issues in the social field and gender issues in the economic field. Lack of commitment from the central, provincial and district/city governments in carrying out their duties, scope and the existence of strategies implemented regarding gender equality.